The predicting factors of clinical outcomes in patients with COVID-19 in the Kingdom of Saudi Arabia [KSA]: A multi-center cohort study - Alrefaee, Janan; E Albalawi, Aishah; Alanazi, Sarah; A Althobaiti, Norah; Daghash, Hanan; Abu Hasb, Tharaa; Abusuliman, Mohammad (Journal of the Faculty of Medicine Baghdad, 2022)
Background: On March 2020, the first case of coronavirus disease-19 was registered in the Kingdom of Saudi Arabia and subsequently the first mortality case. The predicting factors for patients' outcomes are essential to triage patients with COVID-19. This may provide low-cost facilities that help in the fight against the existing global pandemic.   Objectives: This study aimed to predict hospitalization and death outcomes of COVID-19 patients using the simplest facilities.Method: The electronic medical records of 280 COVID-19 patients between March 2020 and May 2021 were retrieved from a multi-centre of healthcare facilities across Kingdom of Saudi Arabian cites. All demographic and clinical information were examined to determine predictors and outcomes.Results: Of the 280 COVID -19 patients enrolled in our study, 14.3% were aged ≥ 66 years and 62.5% were female. The elderly (≥ 66 years, P= 0.000) and male patients (P= 0.001) were significantly hospitalized by COVID -19 than others. Patients with symptoms were hospitalized significantly more than patients without symptoms (P= 0.001). Patients with chronic conditions were hospitalized more frequently (P= 0.001). Hospitalization status also did not differ by smoking. Fever occurred significantly more frequently in patients with one or more chronic diseases (P = 0.000). Elderly (≥ 66 years, P= 0.000) and male patients of COVID -19 (P= 0.022) had significant evidence of association with death outcome than others. Hospitalization status was associated with death (P = 0.000).Conclusion: This study reported that male gender and advanced age COVID-19 patients are independent predictors for both hospital admission and death outcomes more than others. The COVID-19 patients who complain from symptoms are at risk for hospitalization as well. Additionally, having chronic clinical conditions are predictor factor for hospital admission outcome. Finally, the hospitalized patients of COVID-19 infection are at risk for death outcome.